Anti-tumor and anti-angiogenic effects of metronomic dosing of BH3-mimetics - Imai, Atsushi (2011)
Recent studies have shown that Bcl-2 functions as a pro-angiogenic signaling molecule in addition to its well-known effect as an inhibitor of apoptosis. The discovery of AT101, a BH3-mimetic drug that is effective and well tolerated when administered orally, suggested the possibility of using a molecularly targeted drug in a metronomic regimen. Here, we generated xenograft squamous cell carcinomas (SCC) with humanized vasculature in immunodeficient mice. Mice received taxotere in combination with either daily 10 mg/kg AT101 (metronomic regimen) or weekly 70 mg/kg AT101 (bolus regimen). The effect of single drug AT101 on angiogenesis, and combination AT101/taxotere on the survival of endothelial cells and SCC cells, were also evaluated in vitro. Metronomic AT101 increased mouse survival (p=0.02), decreased tumor mitotic index (p=0.0009), and decreased tumor microvessel density (p=0.0052), as compared to bolus delivery of AT101. Notably, the substantial potentiation of the anti-tumor effect observed in the metronomic AT101 group was achieved using the same amount of drug and without significant changes in systemic toxicities. In vitro, combination of AT101 and taxotere showed additive toxicity for endothelial cells and synergistic or additive toxicity for tumor cells (SCC). Interestingly, low-dose (sub-apoptotic) concentrations of AT101 potently inhibited the angiogenic potential of endothelial cells. Taken together, these data unveiled the benefit of metronomic delivery of a molecularly targeted drug, and suggested that patients with squamous cell carcinomas might benefit from continuous administration of low dose BH3-mimetic drugs.